2015
DOI: 10.1007/s12011-015-0555-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Insulin Signaling in Bone Turnover Induced by Fluoride

Abstract: The role of insulin signaling on the mechanism underlying fluoride induced osteopathology was studied. We analyzed the expression of genes related with bone turnover and insulin signaling in rats treated by varying dose of fluoride with or without streptozotocin (STZ) in vivo. Furthermore, insulin receptor (InR) expression in MC3T3-E1 cells (pre-osteoblast cell line) was interfered with small interfering RNA (siRNA), and genes related with osteoblastic and osteoclastic differentiation were investigated in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…However, excessive fluoride may result in skeletal fluorosis, a condition that patients display various bone lesions including osteosclerosis, osteoporosis and degenerative joint changes [ 4 , 5 ]. Although some investigators have reported many studies in fluoride and bone turnover [ 6 , 7 ], the pathogenic mechanism of the skeletal fluorosis was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive fluoride may result in skeletal fluorosis, a condition that patients display various bone lesions including osteosclerosis, osteoporosis and degenerative joint changes [ 4 , 5 ]. Although some investigators have reported many studies in fluoride and bone turnover [ 6 , 7 ], the pathogenic mechanism of the skeletal fluorosis was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…4A). Moreover, DEmiR-targeted DEGs were significantly involved in pathways, such as the peroxisome proliferator-activated receptor (PPAR) and insulin signaling pathways (26,27) (Fig. 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Liu et al [37] performed in rats treated with fluoride suggest that osteoblasts are more sensitive to the toxic action of high dose of fluoride than osteoclasts. Indeed, the decreased bone area of the proximal tibial epiphysis observed in OVX-F group highlights the fact that fluoride treatment did not improve the quality of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The higher intensity of immunostaining for OCN in OVX-F animals compared to control observed in the present study corroborate the findings of Sun et al [32] who observed increased OCN expression in bone tissue of rats exposed to fluoride (20 mg/kg/day) for two months. Recent studies performed in cultured bone cells obtained from femurs of rats treated with fluoride suggest that this element can stimulate OCN production by activation of the insulin receptor signaling pathway in osteoblasts [37].…”
Section: Discussionmentioning
confidence: 99%